Straight leg elevation to rule out pelvic injury. Issue 2 (February 2018) - Bolt, Caroline; O'Keeffe, Francis; Finnegan, Pete; Dickson, Kristofer; Smit, De Villiers; Fitzgerald, Mark C.; Mitra, Biswadev
Abstract: Objective: Pelvic x-ray is frequently used as a screening tool during initial assessment of injured patients. However routine use in the awake and alert blunt trauma patient may be questioned due to low yield. We propose a clinical tool that may avoid unnecessary imaging by examining whether the ability to straight leg raise, without pain, can rule out pelvic injury. Methods: We conducted a prospective cohort study with the exposure variables of ability to straight leg raise and presence of pain on doing so, and presence of pelvic fracture on x-ray as the primary outcome variable. Results: Of the 328 participants, 35 had pelvic fractures, and of these 32 were either unable to straight leg raise, or had pain on doing so, with a sensitivity of 91.43% (95% CI: 76.94–98.2%) and a negative predictive value of 98.57% (95% CI: 95.88–99.70%). The 3 participants with a pelvic fracture who could straight leg raise with no pain, all had a GCS of less than 15, and therefore, among the sub-group of patients with GCS15, a 100% sensitivity and 100% negative predictive value for straight leg raise with no pain to rule out pelvic fracture was demonstrated. Conclusion: Among awake, alert patients, painless straight leg raise can exclude pelvic fractures and be incorporated into initial examination during reception and resuscitation of injured patients.